The influence of specimen thickness and alignment on the material and failure properties of electrospun polycaprolactone nanofiber mats. Issue 11 (14th July 2016) - Mubyana, Kuwabo; Koppes, Ryan A.; Lee, Kristen L.; Cooper, James A.; Corr, David T.
Abstract: Electrospinning is a versatile fabrication technique that has been recently expanded to create nanofibrous structures that mimic ECM topography. Like many materials, electrospun constructs are typically characterized on a smaller scale, and scaled up for various applications. This established practice is based on the assumption that material properties, such as toughness, failure stress and strain, are intrinsic to the material, and thus will not be influenced by specimen geometry. However, we hypothesized that the material and failure properties of electrospun nanofiber mats vary with specimen thickness. To test this, we mechanically characterized polycaprolactone (PCL) nanofiber mats of three different thicknesses in response to constant rate elongation to failure. To identify if any observed thickness‐dependence could be attributed to fiber alignment, such as the effects of fiber reorientation during elongation, these tests were performed in mats with either random or aligned nanofiber orientation. Contrary to our hypothesis, the failure strain was conserved across the different thicknesses, indicating similar maximal elongation for specimens of different thickness. However, in both the aligned and randomly oriented groups, the ultimate tensile stress, short‐range modulus, yield modulus, and toughness all decreased with increasing mat thickness, thereby indicating that these are not intrinsic material properties. These findings have important implications in engineered scaffolds for fibrous and soft tissue applications (e.g., tendon, ligament, muscle, and skin), where such oversights could result in unwanted laxity or reduced resistance to failure. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 104A: 2794–2800, 2016.